The Distinct Function of p21Waf1/Cip1 With p16Ink4a in Modulating Aging Phenotypes of Werner Syndrome by Affecting Tissue Homeostasis - Zhang, Yongjin; Shao, Chihao; Li, Haili; Wu, Kun; Gong, Lixin; Zheng, Quan; Dan, Juhua; Jia, Shuting; Tang, Xiaodan; Wu, Xiaoming; Luo, Ying (Frontiers in Genetics, 2021)
Human Werner syndrome (WS) is an autosomal recessive progeria disease. A mouse model of WS manifests the disease through telomere dysfunction-induced aging phenotypes, which might result from cell cycle control and cellular senescence. Both p21Waf1/Cip1 (p21, encoded by the Cdkn1a gene) and p16Ink4a (p16, encoded by the Ink4a gene) are cell cycle inhibitors and are involved in regulating two key pathways of cellular senescence. To test the effect of p21 and p16 deficiencies in WS, we crossed WS mice (DKO) with p21-/- or p16-/- mice to construct triple knockout (p21-TKO or p16-TKO) mice. By studying the survival curve, bone density, regenerative tissue (testis), and stem cell capacity (intestine), we surprisingly found that p21-TKO mice displayed accelerated premature aging compared with DKO mice, while p16-TKO mice showed attenuation of the aging phenotypes. The incidence of apoptosis and cellular senescence were upregulated in p21-TKO mice tissue and downregulated in p16-TKO mice. Surprisingly, cellular proliferation in p21-TKO mice tissue was also upregulated, and the p21-TKO mice did not show telomere shortening compared with age-matched DKO mice, although p16-TKO mice displayed obvious enhancement of telomere lengthening. Consistent with these phenotypes, the SIRT1-PGC1 pathway was upregulated in p16-TKO but downregulated in p21-TKO compared with DKO MEFs. However, the DNA damage response pathway was highly activated in p21-TKO, but rescued in p16-TKO, compared with DKO MEFs. These data suggest that p21 protected the stem cell reservoir by regulating cellular proliferation and turnover at a proper rate and that p21 loss in WS activated fairly severe DDR responses, which might cause an abnormal increase in tissue homeostasis. On the other hand, p16 promoted cellular senescence by inhibiting cellular proliferation, and p16 deficiency released this barrier signal without causing severe DDR.